The Interest and Action of Young Agricultural Entrepreneur on Agribusiness in Cianjur Regency, West Java - Harniati Harniati; Oeng Anwarudin (Jurnal Penyuluhan, 2018)
Slow succession of the agricultural actors should be solved immediately. The research objective is to analyze descriptively the interest and action of young agricultural entrepreneur (agripreneur) on agribusiness and some factors influencing the interest and action of young agripreneur on agribusiness. The research was conducted in Cianjur Regency of West Java on March 2017 until October 2017. The population in the research was the young agripreneur as the agricultural actors. The sample consisted of 83 persons who were chosen by using multi stage random sampling. The variable of the research consisted of age, formal education level, educational background, non-formal education level, farming experience, farming motivation, community support, level of facility and infrastructure availability, financial institution support, extension agency support, source of information support, extension activity, entrepreneurial capacity, interest and action of the young agripreneur. The data were analyzed by using descriptive statistics and multiple regression analysis. The result shows that the average of interest and action of young agripreneur on agribusiness are categorized in high position. The interest of young agripreneur is influenced by non-formal education level, motivation, community support, source of information support, and entrepreneurial capacity. The action of young agripreneur is influenced by non-formal education, motivation, community support, source of information support, entrepreneurial capacity, and the interests of young agripreneur on agribusiness field.